Wide-genome selection of lactic acid bacteria harboring genes that promote the elimination of antinutritional factors - Pham, Hai-Ha-Thi; Kim, Do-Hyung; Nguyen, Thanh Luan (Frontiers in Plant Science, 2023)
Plant-based products such as soybean, sunflower, canola, and wheat are characterized by an amino acid imbalance and high quantities of anti-nutritional factors (ANFs) substances. Among of well-known ANFs, indigestible non-starchy polysaccharides (α-galactooligosaccharides, α-GOS), phytate, tannins, and alkaloids can impede the absorption of many critical nutrients and cause major physiological disorders. To enhance silage quality and its tolerance threshold for humans as well as other animals, ANFs must be reduced. This study aims to identify and compare the bacterial species/strains that are potential use for industrial fermentation. Among four pan-genomes analysis, all 37 tested Bacillus subtilis genomes had one phytate degradation gene, while 91 out of 150 Enterobacteriacae genomes harbor at least one genes (maximum three). Although, no gene encoding phytase detected in genomes of Lactobacillus and Pediococcus species, they have genes involving indirectly in metabolism of phytate-derivatives to produce Myo-inositol, an important compound in animal cells physiology. In contrast, genes related to production of lectin, tannase and saponin degrading enzyme did not include in genomes of B. subtilis and Pediococcus species. Our findings suggest a combination of bacterial species and/or unique strains in fermentation, for examples, two Lactobacillus strains (DSM 21115 and ATCC 14869) with B. subtilis SRCM103689, would maximize the efficiency in reducing the ANFs concentration. In conclusion, this study provides insights into bacterial genomes analysis for maximizing nutritional value in plant-based food. Further investigations of gene numbers and repertories correlated to metabolism of different ANFs will help clarifying the efficiency of time consuming and food qualities.